EVALUASI KINERJA STRUKTUR GEDUNG RUMAH SAKIT 7 LANTAI 1 BASEMENT DI SEMARANG DENGAN ANALISIS DINAMIK LINEAR RESPONS RAGAM DAN RIWAYAT WAKTU MENGGUNAKAN ACUAN SNI 1726:2019 - Handayani, Nur Khotimah; Abadi, Bestari Mukti; Pamungkas, Nova Dwi (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2024)
Structural planning in buildings must be carried out correctly to avoid structural failure. Hospital Building 7 Floor 1 Basement is a building which is a public health facility and is a building in Risk Category IV. This building was planned using the old earthquake regulations, namely SNI 1726:2012, so it needs to be evaluated using the latest earthquake regulation standards, namely SNI 1726:2019. This evaluation is carried out to ensure that the structure still meets the standards of the new regulations. The analysis procedure used is linear dynamic analysis of variance response and time history using 4 earthquake records, namely the Duzce, Iwate, Whittier and Chichi earthquakes. Structural analysis was calculated using ETABS V.21 software in a 3-dimensional model. The results of the analysis carried out are base shear and displacement values. Based on the research that has been carried out, it is concluded that the structure has torsional irregularities, internal corner irregularities, irregularities due to shifts perpendicular to the plane, heavy irregularities, and excessively weak story irregularities due to discontinuities in the lateral strength of the story. In addition, it was concluded that in the response analysis procedure the various deviation values did not meet the deviation between permit levels for structures with risk category IV starting on the 2rd floor. Meanwhile, the deviation values between levels produced in the time history dynamic analysis procedure met all floors. The difference in deviation results between the variance response and time history analysis procedures is due to the time history analysis using deviation values based on the combined displacement response which takes into account unexpected torque.